2020
DOI: 10.1016/j.labeco.2020.101877
|View full text |Cite
|
Sign up to set email alerts
|

Parental proximity and earnings after job displacements

Abstract: Young adults, ages 25 to 35, who live in the same neighborhoods as their parents experience stronger earnings recoveries after a job displacement than those who live farther away. This result is driven by smaller on-impact wage reductions and sharper recoveries in both hours and wages. We show that geographic mobility, different job search durations, housing transfers, and ex-ante differences between individuals are unlikely explanations. Our fi ndings are consistent with a framework in which some individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…For the US, Compton and Pollak (2014) found that living close to their own mother, and in this case also to their mother-in-law, increases the probability of mothers of young children to work. Also for the US, Krolikowski et al (2020) showed that after losing a job, young people living in the same neighborhood as their parents benefit from stronger earnings recovery and that this is mainly driven by childcare. In addition to these mostly positive effects, there might also be downsides to relying on grandparents for childcare.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For the US, Compton and Pollak (2014) found that living close to their own mother, and in this case also to their mother-in-law, increases the probability of mothers of young children to work. Also for the US, Krolikowski et al (2020) showed that after losing a job, young people living in the same neighborhood as their parents benefit from stronger earnings recovery and that this is mainly driven by childcare. In addition to these mostly positive effects, there might also be downsides to relying on grandparents for childcare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, as wage growth and human capital investments flatten out with age (Ben-Porath, 1967;Becker, 1981), having grandparents to provide childcare for them would incur lower family-wide opportunity costs than if the mothers themselves stopped working. It might thus be rational for grandparents to reduce working hours and give up labor earnings so that their daughter can invest in her lifetime earnings while she is still in the phase of steep wage growth (see Krolikowski et al, 2020). Hence, the availability of grandparents to supply childcare depends on their own employment and living situation (Hank & Buber, 2009;Bratti et al, 2018).…”
Section: Economic Activitymentioning
confidence: 99%
“…As Rodrik (2007) emphasizes, many of these policies are targeted on firms and industries that would be in difficulties even in the absence of the program, so naïve ordinary least squares (OLS) estimates may miss any positive effects. 2 We tackle the identification problem by exploiting a policy experiment that induced exogenous changes in the eligibility criteria governing whether plants in economically disadvantaged areas could receive investment subsidies from a major subsidy program in the United Kingdom. This program was called Regional Selective Assistance (RSA), but similar support programs exist in other European Union (EU) countries.…”
mentioning
confidence: 99%
“…Moreover, they also find that an increase in welfare benefits affects the provision of parental support in terms of transfers and coresidence (Rosenzweig and Wolpin, 1994). Krolikowski et al (2020) extend the idea of coresidence by studying the effect of living in the same neighborhood as parents on earnings. They find that young people who live close to their parents experience stronger earnings recoveries after a job displacement than those who live farther away.…”
Section: Introductionmentioning
confidence: 93%